Designing a Humanistic Arabic Speaking Textbook for Rural Islamic School Students: A Maslow-Based Approach - Wazkia, Hanif; Rasyidi, Abdul Wahab; Mufidah, Nuril (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to develop and evaluate an Arabic speaking textbook for rural Islamic school students based on Abraham Maslow’s -humanistic approach. This approach was chosen to address students’ weak speaking proficiency caused by the dominance of traditional teaching methods that emphasize rote memorization and grammar, as well as the lack of opportunities for meaningful and contextual communication. The research applied a Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Qualitative information was gathered through observations, interviews, and expert assessments, while quantitative data were collected via pretest–posttest evaluations and questionnaires. The results show that the textbook is highly practical and well-received, with expert validation scores above 85% and positive student responses, including enhanced motivation, participation, and self-confidence in speaking. Statistical analysis revealed significant improvement in the experimental group, with an average N-Gain of 0.72. Overall, the study indicates that a textbook designed with attention to students’ psychological needs—such as security, social connection, and self-esteem—can effectively support the development of Arabic speaking skills in junior secondary students.